2022
DOI: 10.3892/etm.2022.11183
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous lesions associated with SARS‑CoV‑2 infection (Review)

Abstract: The ongoing COVID-19 pandemic, declared by the World Health Organisation in March 2020, with the emergence of new, possibly more contagious and more virulent strains, remains a research subject, with the complex systemic involvement better described and understood, but also with a variety of skin and mucosal lesions described in the literature. Mucocutaneous lesions associated with SARS-CoV-2 infection are still under investigation, due to their polymorphic clinical aspect and incompletely understood pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Cutaneous manifestations of COVID-19 occur in 1% to 5.7% of cases [ 48 , 49 , 50 ] and the five most common patterns of skin lesions identified in patients with COVID-19 were: pseudo-chilblains (40.9%), maculopapular rash (27.9%), urticarial (12.5%), vesicular (10.7%), and vaso-occlusive lesions (4.4%) [ 48 , 51 ].…”
Section: The Role Of Viral Infections Including Covid-19 In Causing A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous manifestations of COVID-19 occur in 1% to 5.7% of cases [ 48 , 49 , 50 ] and the five most common patterns of skin lesions identified in patients with COVID-19 were: pseudo-chilblains (40.9%), maculopapular rash (27.9%), urticarial (12.5%), vesicular (10.7%), and vaso-occlusive lesions (4.4%) [ 48 , 51 ].…”
Section: The Role Of Viral Infections Including Covid-19 In Causing A...mentioning
confidence: 99%
“…The urticarial rash associated with COVID-19 was reported in numerous publications ranging from 1.9% to 19% [ 43 , 49 , 50 , 52 , 53 ]. Urticaria usually appears simultaneously with systemic symptoms, lasts ~1 week, and predominantly involves the trunk and the limbs and spares acral sites affecting mostly adolescents/young adults [ 51 , 54 ].…”
Section: The Role Of Viral Infections Including Covid-19 In Causing A...mentioning
confidence: 99%
“…The pathogenesis of SARS-CoV-2-associated livedo racemosa remains unclear, but a few pathogenic hypotheses have been posited. One is the inhibition of type I interferon response, in which the binding of single-stranded RNA of the SARS-CoV-2 virus to toll-like receptors 7 and 8 promotes the production of type I interferons [ 42 , 43 ]. Interferons are then secreted and bound to the homodimer receptors of type I interferons.…”
Section: Pathogenesis Of Covid-19-related Skin Diseases and Therapeut...mentioning
confidence: 99%
“…STAT1, which plays a pivotal role in signal transduction and transcriptional activation, is then phosphorylated and activated. STAT2, which initiates the generation of a host of protective proteins, such as interferon-induced transmembrane protein (IFITM) 3, is also phosphorylated, promoting its ability to reduce COVID-19 outcomes [ 43 ]. In patients with COVID-19, it has been confirmed that the type I interferon response is minimal [ 42 ].…”
Section: Pathogenesis Of Covid-19-related Skin Diseases and Therapeut...mentioning
confidence: 99%
See 1 more Smart Citation